Carl Th. Dreyer - My Metier - Jensen, Torben Skjodt; Paalgard, Harald (BFI, 2006)
Torben Skjodt Jensen's elegant documentary is a collage of memories and reflections on one of cinema's greatest directors. Visually rich and densely layered, "Carl Th. Dreyer - My Metier" illuminates an artist too little understood and too important to overlook. Through interviews, historical writings, and rare archival footage, a portrait of Dreyer emerges an austere perfectionist, yes, but also a passionate man possessing a genuine sense of humor. Shot in 35mm black and white, the documentary's narrative is rich in content. The participants in these pieces are the actors, film crew, and colleagues who have worked with Dreyer: Birgitte Federspiel, Preben Lerdorff Rye, Lisbeth Movin, Axel Strøbye, Baard Owe, Henning Bendtsen, and Jørgen Roos. In addition, Helene Falconetti, daughter of the renowned Falconetti, discusses her mother's role in "The Passion of Joan of Arc". [www.tcm.com]